My God is not your God: the role of media in handling the uproar caused by the used of 'Allah' by non-Muslims in Malaysia - Ahmad, Abd Mua'ti @ Zamri (Pacific and Asian Communication Association, 2013)
In late 2007, the Home Ministry of Malaysia has banned the use of the word 'Allah' by the Herald, a Catholic newsletter. The ministry later confiscated 15,000 copies of Malay language Bibles imported from Indonesia in which the word for God is translated as 'Allah'. The reason is 'to avoid the Muslims from being confused' when the non-Muslims talk about their God. In other words the authorities in Malaysia consider the word 'Allah' is monopolized only by the Muslims. Nevertheless, on December 31, 2009 a ruling by the Kuala Lumpur High Court overruled the earlier ban, asserting constitutional guarantees regarding the freedom of religion in Malaysia. Since then, an already tense situation boiled over, largely due to incitement by a few hasty politicians, the mainstream media and a handful of non-governmental organizations linked by membership and leadership to the United Malays National Organization, the major ruling party. Consequently, Malaysians ushered the New Year by witnessing arsonists and vandal attacks on about ten places of worship, including Christian churches, a Sikh temple, Muslim prayer rooms and mosques. Though there were no physical injuries to anyone and the material damage can be repaired, the same cannot be said about the emotional and psychological wound left behind in the people. After numerous conflicting statements from political leaders and government officials, the underlying causes of the violence were still left unaddressed. Malaysia's reputation as a nation at peace with its ethnic and religious diversity is at stake. In the light of this conflict, what is the role of communication media in the country? Specifically how has the media being used to control the uproar from being escalated into a more chaotic situation? This paper attempts to address the questions, through a study performed on main news media throughout the turbulence in January and February 2010.